Evaluation of a red‐blood‐cell genotyping platform, ID CORE XT, within a hospital transfusion service. (23rd May 2019) - Hayes, Chelsea; Seo, Jina; Abumuhor, Ihab; Klapper, Ellen
Abstract : Background and Objectives: Red‐blood‐cell genotyping is used to provide extended matched blood, resolve typing discrepancies and predict phenotype in recently transfused patients or patients with a positive direct antiglobulin test. The aim of this study was to complete a performance and operational evaluation of a genotyping system, ID CORE XT (Progenika Biopharma–Grifols, Barcelona, Spain), within a hospital transfusion service, using the current genotyping method as a reference for comparison. Materials and Methods: DNA was extracted from blood donor and patient samples and tested using ID CORE XT and the reference method. Predicted RBC phenotype, turnaround time and hands‐on time were compared. A questionnaire was administered to each clinical laboratory scientist to evaluate each platform's ease of use. Results: A total of 438 samples were tested and overall agreement between methods was 99·99%, with a single M antigen typing discrepancy noted. DNA sequencing revealed that ID CORE XT incorrectly designated the antigen status as M‐negative, resulting in a false‐negative M antigen predicted phenotype result. ID CORE XT showed a 24·5% and 51·3% reduction in mean turnaround time and hands‐on time, respectively, as compared to the reference method. Conclusion: ID CORE XT and the reference method are highly concordant regarding predicted phenotype. ID CORE XT offers several operational advantages, making it suitable for a busy hospital transfusion service.